2021
DOI: 10.1186/s12888-021-03253-8
|View full text |Cite
|
Sign up to set email alerts
|

Venlafaxine vs. fluoxetine in postmenopausal women with major depressive disorder: an 8-week, randomized, single-blind, active-controlled study

Abstract: Background In the population of postmenopausal patients with major depressive disorder (MDD), the superiority of serotonin-norepinephrine reuptake inhibitors (SNRIs) over selective serotonin reuptake inhibitors (SSRIs) has not yet been definitively proven. Consequently, a direct comparison of the efficacy of SSRIs and SNRIs in the treatment of postmenopausal depression could provide relevant data. The aim of this study was to compare the efficacy and safety of venlafaxine vs. fluoxetine in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Effects in HAMD-24 depression feature score and Clinical Global Impressions-Improvement (CGI-I) were obtained to measure the secondary outcomes. The efficacy was analyzed utilizing the Full Analysis Set (FAS) and the modified intentionto-treat (mITT) principle [6].…”
Section: Antidepressantmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects in HAMD-24 depression feature score and Clinical Global Impressions-Improvement (CGI-I) were obtained to measure the secondary outcomes. The efficacy was analyzed utilizing the Full Analysis Set (FAS) and the modified intentionto-treat (mITT) principle [6].…”
Section: Antidepressantmentioning
confidence: 99%
“…There was no discernible difference between the two groups with regards to adverse effects. The trials have shown that venlafaxine is better adapted and has a better effect on the treatment of postmenopausal MDD [6].…”
Section: Antidepressantmentioning
confidence: 99%
“…The sample size was small; this might have influenced the results and conclusion of this study. Moreover, Venlafaxine is the first of the SNRIs that provides dose-dependent norepinephrine reuptake inhibition; a dosage of 150 mg/day or higher is sufficient to produce noradrenergic activity, and it has low affinity for the postsynaptic receptors ( Strawn et al, 2018 ; Zhou et al, 2021 ). A latest review has demonstrated that the brain function changes at least 4 weeks’ antidepressant pharmacotherapy in patients with MDD ( Cattarinussi et al, 2021 ).…”
Section: Limitationsmentioning
confidence: 99%
“…Fluoxetine (FLX), a selective serotonin reuptake inhibitor (SSRI), has been used to treat depression, anxiety and even premature ejaculation ( Kryst et al, 2022 ; Liu et al, 2022 ; Zhou et al, 2021 ). Compared to tricyclic antidepressants or monoamine oxidase inhibitors, SSRIs are less toxic, but there are still articles reporting that they can inhibit Na + , Ca 2+ , and K + channels during treatment ( Bruggeman et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%